2017
DOI: 10.14419/ijm.v5i1.7280
|View full text |Cite
|
Sign up to set email alerts
|

Natural products in green-detection of cancer cells, cancer therapy, and monitoring of therapeutic and cancer progression: A perspective

Abstract: The natural products embedded with the molecular framework by combining with themselves or other molecules and biological micro/macro molecules. By the help of some special techniques, that can be incorporated to identify and detect different body markers as well as pathophysiological conditions. To date, a number of cancer detection methods are available. However, an early cancer detection is still remained the key problems, which causes delay, reduction of success rate in the cancer therapy, and increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There are approximately 25-125 seeds that remain within a fruit 2 . Similarly, Chaudhuri and Choudhury reported that there are approximately 30-60 seeds that remain within a fruit 3 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…There are approximately 25-125 seeds that remain within a fruit 2 . Similarly, Chaudhuri and Choudhury reported that there are approximately 30-60 seeds that remain within a fruit 3 .…”
Section: Introductionmentioning
confidence: 91%
“…S. apetala is a plant species that undergoes pollination by various organisms such as moths 19 , bats 25 , honeybees, and other insects 3 . Birds were also identified as pollinators by Backer and Steenis in 1948.…”
Section: Reproductive Featuresmentioning
confidence: 99%